T cell responses to Mycobacterium indicus pranii immunotherapy and adjunctive glucocorticoid therapy in tuberculous pericarditis. (August 2022) - Steigler, Pia; Chhiba, Mukesh; Francis, Veronica; Keyser, Alana; Abrahams, Deborah; Hanekom, Willem; Ntsekhe, Mpiko; Scriba, Thomas J.
Abstract: Background: In the Investigation of the Management of Pericarditis (IMPI) randomized control, 2x2 factorial trial, Mycobacterium indicus pranii ( MIP ) immunotherapy, adjunctive corticosteroids or MIP combined with corticosteroids was compared to standard tuberculosis (TB) therapy for tuberculous pericarditis (TBP). While MIP and/or the combination of MIP and corticosteroids had no impact on all-cause mortality or pericarditis related outcomes, corticosteroids reduced the incidence of constrictive pericarditis at 12 months. Data suggests that both adjunctive therapies modulate the immune and inflammatory responses to pulmonary TB. Whether they affect systemic antigen-specific T cell responses, key immune mediators of Mycobacterium tuberculosis control, in patients with TBP is unknown. Methods: Participants with definite or probable TBP were randomly assigned to receive five injections of MIP or placebo at 2-week intervals and either 6 weeks of oral prednisolone or placebo. Frequencies of CD4 and CD8 T cells expressing IFN-γ, IL-2 or TNF in response to MIP or purified protein derivative stimulation were measured by intracellular cytokine staining and flow cytometry up to 24 weeks post treatment. Results: Immunotherapy with MIP did not significantly modulate frequencies of Th1 CD4 and CD8 T cells compared to placebo. Adjunctive prednisolone also did not change mycobacteria-specific CD4 or CD8 T cell responses. By contrast, combinatorial therapy with MIP and prednisolone was associated with a modest increase in frequencies of multifunctional and single cytokine-expressing CD4 T cell responses at 6 and 24 weeks post treatment. Conclusions: Consistent with the lack of a significant clinical effect in the IMPI trial, MIP immunotherapy did not significantly modulate mycobacteria-specific T cell responses. Despite the positive effect of prednisolone on hospitalizations and constrictive pericarditis in the IMPI trial, prednisolone did not significantly reduce pro-inflammatory T cell responses in this sub-study. The modest improvement of mycobacteria-specific T cell upon combinatorial therapy with MIP and prednisolone requires further investigation.